Evaluation of Phenotypic Methods for the Detection of Methicillin-resistant Staphylococcus aureus in Comparison with PCR - Khatun, Aysha; Saha, Ritu; Salauddin, Gazi Mohammad; Alam, Fatema Mohammad; Afroz, Sonia; Ahmed, Sharmeen (Bangladesh Journal of Infectious Diseases, 2026)
Background: The major cause of hospital- and community-acquired infections is Methicillin-resistant Staphylococcus aureus (MRSA). Early and specific identification is important for effective treatment and infection management. While PCR for mecA is the gold standard, its use is often restricted in routine laboratories due to high costs and technical limitations. Objective: The objective of this research was to assess the efficacy of widely used phenotypic approaches for MRSA identification and to compare them with PCR. Methodology: This cross-sectional study was conducted from March 2016 to February 2017 at the Department of Microbiology and Immunology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh. A total of 120 clinically confirmed Staphylococcus aureus isolates were collected from DMC, BIRDEM, and BSMMU microbiology laboratories. MRSA detection was performed using four phenotypic methods: oxacillin disk diffusion, cefoxitin disk diffusion (CLSI 2014 guidelines), MRSA chromogenic agar (HiCrome MeReSa), and latex agglutination test (Denka-Seiken PBP2a kit). PCR targeting the mecA gene, using the QIAamp DNA Mini Kit for extraction and electrophoresis on 3% agarose gel, served as the gold standard reference method. Sensitivity, specificity, accuracy, positive predictive value (PPV), and negative predictive value (NPV) were calculated and compared across all methods. Results: PCR identified 70(58.3%) MRSA and 50(41.7%) MSSA among 120 Staphylococcus aureus isolates. Cefoxitin disk diffusion showed great performance of 92.9% sensitivity and 98.0% specificity, while MRSA chromogenic agar showed 90.0% sensitivity and specificity. The oxacillin disk diffusion test was the least sensitive test, with a sensitivity of 81.4%. Latex agglutination test is the best test, with 100% sensitivity, specificity and overall accuracy. Conclusion: Latex agglutination was the quickest and most accurate phenotypic approach, similar to the PCR finding exactly. Cefoxitin disk diffusion was also a good alternative. Using these strategies may help to identify MRSA and stop the spread of infections with limited resources. Bangladesh Journal of Infectious Diseases, December 2025;12(2):294-299